New records of genus Scenedesmus (Chlorophyceae) found in Korea - Yong Jae Kim (Journal of Ecology and Environment)
This study summarizes the taxonomic notes and distribution of 13 taxa of the genus Scenedesmus(Chlorophyceae) collected from several swamps, reservoirs, and rivers throughout South Korea from 2012 to 2014. In this study, light microscopy images of all 13 taxa are presented and briefly discussed with regard to their taxonomy, distribution, and ecology and environmental factors of occurrence sites. All 3 subgenera (subgenusScenedesmus1 taxon; subgenus Acutodesmus2 taxa; subgenusDesmodesmus10 taxa) are newly described in Korean freshwater algal flora:S. linearis, S.acuminatusvar. elongatus, S. acuminatusvar.tetradesmoides, S. carinatus, S. denticulatusvar.disciformis, S. gutwinskiivar. heterospina, S. helveticusf.bicaudatus, S. lefevrei, S. oahuensisvar. clathratusf.longiclathratus, S. oahuensisvar . clathratus, S. pan nonicus, S. polydenticulatus,and S. tenuispina.